A Highly Stable Luminescent Eu‐MOF Exhibiting Efficient Response to Nitrofuran Antibiotics through the Inner Filter Effect and Photoinduced Electron Transfer. Issue 48 (23rd December 2019) - Yang, Han‐Wen; Xu, Ping; Ding, Bo; Liu, Zheng‐Yu; Zhao, Xiao‐Jun; Yang, En‐Cui
Abstract : A novel 4, 8‐connected Eu‐MOF with paddle wheel‐shaped Eu2 (COO)4 subunits extended by 4‐connected BTCTB 3– linkages is hydrothermally synthesized by incorporating with C 3 ‐symmetric 3, 3 ′, 3 ′′ ‐[1, 3, 5‐benzenetriyltris(carbonylimino)]tris‐benzoate ligand (BTCTB), which exhibits high stability, good dispersion and intense red emission. Resulting significantly from the synergetic inner filter effect and photoinduced electron transfer, the framework shows rapid and efficient fluorescence decay towards nitrofuran antibiotics with strong quenching constants and low detection limits of (1.27 ± 0.03) × 10 4 m – 1 and 0.67 ± 0.08 µm for nitrofurazone, (2.10 ± 0.03) × 10 4 m – 1 and 0.60 ± 0.06 µm for nitrofurantoin as well as (1.72 ± 0.04) × 10 4 m – 1 and 0.51 ± 0.06 µm for furazolidone. Furthermore, a RGB value‐based colorimetric response application loaded on the mobile device and personal computer platforms is developed, which can potentially fulfil portable and easy probing for nitrofuran antibiotics in water system. Abstract : A highly fluorescent (4, 8)‐connected Eu‐MOF exhibits rapidly and efficiently response towards nitrofuran antibiotics through fluorescence decay, which is further developed into a colorimetric application to monitor the amount of the nitrofuran antibiotics in water.